A Mouse Model of Celiac Disease. Issue 8 (22nd August 2022) - Abadie, Valérie; Khosla, Chaitan; Jabri, Bana
Abstract: The design and use of mouse models that reproduce key features of human diseases are critical to advance our understanding of the pathogenesis of autoimmune diseases and to test new therapeutic strategies. Celiac disease is a unique organ‐specific autoimmune‐like disorder occurring in genetically susceptible individuals carrying HLA‐DQ2 or HLA‐DQ8 molecules who consume gluten. The key histological characteristic of the disease in humans is the destruction of the lining of the small intestine, a feature that has been difficult to reproduce in immunocompetent animal models. This unit describes the DQ8‐D d ‐villin‐IL‐15 transgenic mouse model of CeD, which was engineered based on the knowledge acquired from studying CeD patients' intestinal samples, and which represents the first animal model that develops villous atrophy in an HLA‐ and gluten‐dependent manner without administration of any adjuvant. We provide detailed protocols for inducing and monitoring intestinal tissue damage, evaluating the cytotoxic properties of intraepithelial lymphocytes that mediate enterocyte lysis, and assessing the activation of the enzyme transglutaminase 2, which contributes to the generation of highly immunogenic gluten peptides. Detailed protocols to prepare pepsin‐trypsin digested gliadin (PT‐gliadin) or chymotrypsin‐digested gliadin (CT‐gliadin), which allow antibody detection against native or deamidated gluten peptides, are also provided in this unit. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Induction of celiac‐like disease in DQ8‐D d ‐villin‐IL‐15tg mice Basic Protocol 2 : Histological assessment of villous atrophy Support Protocol 1 : Morphometric assessment of villous/crypt ratio Support Protocol 2 : Evaluation of epithelial cells renewal Support Protocol 3 : Evaluation of the density of intraepithelial lymphocytes Basic Protocol 3 : Analysis of cytotoxic intraepithelial lymphocytes Basic Protocol 4 : Transglutaminase 2 activation and measurement of antibodies against native and deamidated gluten peptides Support Protocol 4 : Preparation of CT‐gliadin Support Protocol 5 : Preparation of PT‐gliadin